ENVOLVIMENTO DAS METALOPROTEINASES E SINTOMAS DA MENOPAUSA: UMA ABORDAGEM EXPERIMENTAL. - MENDES, Lenise Josy Costa (2019)
Introduction: Menopause is related to the diversity of physical and psychic symptoms due to hormonal decline. At this stage, there is a propensity to pathological development due to the disruption of the extracellular matrix, with which they lead to damage and functional alterations in the organism. New pharmacological targets need to be studied so that there may be treatment in order to treat these patients at this stage of life. Objective: This study aimed to evaluate the effects of metalloproteinases on menopausal symptoms. Materials and methods: Wistar rats and Swiss mice were used, with whom they underwent false-operated (SHAM) and ovariectomy (OVX) surgeries, and were then divided into 6 groups: Group 1: SHAM treated with saline, Group 2: SHAM and treated with Doxycycline (gavage), Group 3: OVX and treated with saline, Group 4: OVX and treated with doxycycline, Group 5: OVX and treated with estrus-progestative (subcutaneous), and Group 6: OVX and treated with doxycycline and Estrus-progestative. The animals were treated for 1 month and the following parameters were investigated: body weight, food intake, total and uterine adipose tissue weight, serum levels of calcium, magnesium, alkaline phosphatase, total proteins, total cholesterol, Triglycerides, urea, creatinine, oxaloacetic transaminase (TGO) and Pyruvic transaminase (TGP), in addition, the hot flashes induced by physical exercise were investigated through the treadmill and follow-up of the estrous cycle. Statistical analysis was performed using Bonferroni tests using GraphPad Prism version 6.00 for Windows. A P value <0.05 was considered statistically significant in all analyzes. Results: The animals treated with doxycycline in combination with Estrus-progestatives showed an increase in the levels of alkaline phosphatase, magnesium, cholesterol Total, creatinine and weight of the adipose and uterine tissues. In the same group, we also observed a reduction in the variation of the cutaneous body temperature and an increase in the frequency of the diestrus phase. However, no statistically significant difference was observed with regard to the levels of total serum proteins, urea, triglycerides, TGO, TGP, body weight and feed intake. Conclusion: It is concluded that metalloproteinases have a relevant role selectively in some menopausal symptoms, especially when there is an association of doxycycline Sub-dose with Estrus-progestative therapy. In particular, this group of enzymes can partially participate in the improvement of renal, hepatic, bone and also obesity, uterine and vaginal atrophy and hot flashes.